2007
DOI: 10.5089/9781451867176.001
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Implications of the VAT Reform in the Philippines

Abstract: This Working Paper should not be reported as representing the views of the IMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
2
8
1
Order By: Relevance
“…Projected impacts are even higher for a rise in the VAT rate from 10 to 15 percent. These estimated welfare losses are large compared to results from other studies, including a study conducted in the Philippines by Newhouse and Zakharova (2007) that uses a partial equilibrium model to find welfare losses varying between 2.5 and 2.7 percent. It is worth mentioning that the estimates of welfare losses from the study by Newhouse and Zakharova are unusually low (S. M. Hossain, 1994, 1995, S. Muñoz and S. Cho, 2003, D. Newhouse and D. Zakharova, 2007, P. Roy et al, 2006.…”
Section: Welfare and Equity Impacts Of The Vatmentioning
confidence: 55%
See 2 more Smart Citations
“…Projected impacts are even higher for a rise in the VAT rate from 10 to 15 percent. These estimated welfare losses are large compared to results from other studies, including a study conducted in the Philippines by Newhouse and Zakharova (2007) that uses a partial equilibrium model to find welfare losses varying between 2.5 and 2.7 percent. It is worth mentioning that the estimates of welfare losses from the study by Newhouse and Zakharova are unusually low (S. M. Hossain, 1994, 1995, S. Muñoz and S. Cho, 2003, D. Newhouse and D. Zakharova, 2007, P. Roy et al, 2006.…”
Section: Welfare and Equity Impacts Of The Vatmentioning
confidence: 55%
“…At the same time, they show that a change by 5 percentage points would be less so. Similarly, Newhouse and Zakharova (2007) find that the tax reform in the Philippines is progressive (D. Newhouse andD. Zakharova, 2007, N. Salti andJ.…”
Section: Welfare and Equity Impacts Of The Vatmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, authorities announced plans to spend 30% of the incremental revenue receipts from the VAT reform on infrastructure and social services, which could further ameliorate any adverse distributional effects. Newhouse and Zakharova (2007) who assessed the distributional impact of the E-VAT reform in the Philippines concluded that the reform was progressive and relatively well targeted but a sizable amount of the benefit accrued to high-income households. Households in the bottom quintile enjoy only about 15 percent of the benefit from the package of tax cuts and spending increases, while households in the top quintile enjoy about 30% of the benefit.…”
Section: Impact Of E-vat On Philippinesmentioning
confidence: 99%
“…28 In addition, high payroll taxes tend to 27 Peñalosa and Turnovsky (2005) argue that in developing countries with a large informal economy taxing capital more heavily than labor income could be optimal. 28 In practice, VAT is often only mildly regressive, as argued by Moore (2005) for Slovakia, Dalsgaard (2008) for the Czech Republic and Newhouse and Zakharova (2007) for the Philippines. Moreover, given the fact that richer households tend to find it easier to evade taxes on capital than on consumption, increasing taxation of the latter can be progressive.…”
mentioning
confidence: 99%